Wide Bandgap Based Devices: Design, Fabrication and Applications, Volume II - Verzellesi, Giovanni (MDPI - Multidisciplinary Digital Publishing Institute, 2022)
Wide bandgap (WBG) semiconductors are becoming a key enabling technology for several strategic fields, including power electronics, illumination, and sensors. This reprint collects the 23 papers covering the full spectrum of the above applications and providing contributions from the on-going research at different levels, from materials to devices and from circuits to systems.